Degradation of phenethoxybenzene in sodium hydroxide. Issue 63 (16th June 2016) - Cronin, Dylan; Moghaddam, Lalehvash; Rackemann, Darryn; Bartley, John; Doherty, William O. S.
Abstract : Simple lignin model compounds containing β-O-4 aryl ether linkages have been utilized as a means to understand lignin depolymerisation. Abstract : Simple lignin model compounds containing β-O-4 aryl ether linkages have been utilized as a means to understand lignin depolymerisation. The effects of reaction temperature, time, catalyst concentration, and initial phenethoxybenzene (PEB) concentration on the degradation of PEB in NaOH were investigated. Operating at 300 °C for 1 h resulted in the highest combined yield of the primary products, phenol and styrene, and also resulted in a reduced amount of degradation products formed. The proportion of oligomeric and polymeric materials formed depended on the NaOH concentration, but not on the initial PEB concentration for equal reaction time. The results were used to suggest probable reaction pathways for PEB degradation.